IMPLEMENTASI LITERASI AL-QURAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN PROBLEMATIKANYA BAGI PESERTA DIDIK MAN 1 BUTON - Rowis, Rowis (Universitas Negeri Gorontalo, 2025)
Literacy in the context of education means the ability to develop information and skills through institutions or schools. Literacy can be formed through learning, mastering information, training skills, reading, thinking, understanding, rewriting ideas and evaluating with repeated analysis. This research aims to find out how the implementation of Qur'anic literacy in learning Islamic religious education and its problems for students at MAN 1 Buton Southeast Sulawesi. This research was conducted on January 09, 2024 to February 09, 2024. The informants in this study were the principal, Islamic Religious Education teachers and students. The type of research that researchers use is descriptive qualitative. data through observation, interviews and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing and verification The results of this study indicate that Al-Qur'an literacy at MAN 1 Buton has several activities, namely providing teaching, establishing a Al-Qur'an tahfidz house, providing motivation, channeling interests and talents in the form of memorizing the Al-Qur'an, supporting factors for students are family factors that encourage them, Islamic Education teachers who are firm in implementing the Al-Qur'an literacy program for students. While the inhibiting factor for students is the lack of understanding of the laws of reading. While the supporting factor for the teacher is a sincere intention in providing material. One of the inhibiting factors for teachers is that there are still many students who play cellphones, so this will cause laziness for students.